Etnoscience of Traditional Alcoholic Beverages (Moke Putih) of Ngada East Nusa Tenggara - Limbu, Umbu Nataniel; Bao, Antonia Paulina; Lea, Victoria Coo; Bhae, Christianus Y. N.; Prihatin , Prihatin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Ngada district has a traditional drink called moke putih. Moke putih is a traditional alcoholic beverage made from the Aren’s water (Arenga pinnata Merr.) that is found in Flores. For the people of Ngada, moke putih is a symbol of being kind and harmony, and the consumption of moke has become a lifestyle for most people in there. This drink has a lot of potential because it has strong historical elements and cultural values. The purpose of this research is to know the history, processing, and the connection between moke putih and the culture of Ngada. The research method is a qualitative approach to ethnoscience through purposive sampling techniques and snowball samplings from villages with 10 respondents and data collection through interviews, observations, and documentation. Moke Putih is a traditional drink that has been passed down from generation to generation and is closely related to the culture, customs, and characteristics of the Ngada people. White moke is made from slicing the fruit stalks of the sap tree, and this drink is used at every traditional event and in daily activities as a substitute for drinking water.